2007
DOI: 10.1007/s11482-008-9041-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Demographic Characteristics on Health-related Quality of Life Profile of Malaysian Epilepsy Population

Abstract: The possibilities of adverse drug reactions and disease-related psychosocial implications have led to the current emphasis on health-related quality of life (HRQoL) assessment in epilepsy. The main objective of this study was to determine the impact of various demographic characteristics i.e. gender, age, marital status, ethnic origin, religion, and employment status on HRQoL profiles in Malaysian epilepsy patients. Patients with epilepsy were recruited from ten public hospitals in Sabah, Malaysia. Upon writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It has good reliability and validity and has been used in at least 10 different cultural settings. The Malay version was translated and validated locally (Lua et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…It has good reliability and validity and has been used in at least 10 different cultural settings. The Malay version was translated and validated locally (Lua et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…At the baseline, all patients completed the Personal Information Form, Malay Awareness, Knowledge, Attitudes Epilepsy 5 and Malay Modified Morisky Medication Adherence Scale (MMMMAS). 68 Patients in the control group (CG) received an 11-part printed epilepsy educational module plus a user manual. A total of 12 weeks were needed to complete the entire module (one part per week).…”
Section: Methodsmentioning
confidence: 99%
“…The Malay Modified Morisky Adherence Scale 68 was a simple 4-item questionnaire which asked closed questions on medication use with binary response options (Yes = 0; No = 1). It was designed to gauge adherence level.…”
Section: Methodsmentioning
confidence: 99%
“…Many factors influenced quality of life among patients with epilepsy. Among factors that have been studied in Malaysia were demographic Ahmad Sharoni et al 2013;Anu et al 2016;Din et al 2012d;Fong et al 2018;Lua et al 2008;Norsa'adah et al 2006;2014), clinical (Lua et al 2007;Mohamed et al 2010;2014;Din et al 2012d;Norsa'dah et al 2006;Viswanathan & Abdul Khalid 2004), and psychosocial factors (Mohamed et al 2010;2014;Din et al 2012d;Lua, Neni & Nor Samira 2012). Norsa'adah et al (2006) recruited 65 adult epilepsy patients who attended the Neurology Clinic of HUSM.…”
Section: Factors Influencing Quality Of Life Of Epilepsy Patients In mentioning
confidence: 99%
“…Similar study among 106 adults with epilepsy attending the weekly neurology clinic of Universiti Sains Malaysia Hospital showed that PWE who had one or more seizures in the past four weeks had significantly lower mean score of QOL compared to those who had no seizure after adjusting for age, sex, treatment, duration and age at onset of epilepsy (Norsa'dah et al 2014). Lua et al (2008) conducted a cross-sectional study on 113 epilepsy patients recruited from 10 hospitals in Sabah, Malaysia with the purpose of determining the impact of various demographic characteristics (gender, age, marital status, ethnic origin, religion, and employment status) on QoL. Using the Overall Score of the Malay QOLIE-31 as the dependent variable, the research found that all six demographic factors explained 17.0% of the variance in the Overall QOLIE score.…”
Section: Factors Influencing Quality Of Life Of Epilepsy Patients In mentioning
confidence: 99%